2007
DOI: 10.1111/j.1440-1827.2006.02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma arising in a long pre‐existing angiomyolipoma

Abstract: Angiomyolipoma (AML) is a mixed mesenchymal tumor belonging to the family of perivascular epithelioid cell tumors. Concurrent development of AML and adult renal cell carcinoma (RCC) is very rare. Herein is presented a unique case in which RCC arose within a previously detected AML tumor mass. A 40-year-old woman had been diagnosed with AML of the right kidney. Fifteen years later, during a regular radiographic examination, a new lesion was detected at the lower pole of the right kidney adjacent to the previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…[12] The coexistence of RCC and renal AML within same tumor masses, namely collision tumor, is very rare, and about six cases have been reported. [3] Here, we present a case of a young male with TSC and multiple AMLs, containing RCC with eosinophilic morphology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12] The coexistence of RCC and renal AML within same tumor masses, namely collision tumor, is very rare, and about six cases have been reported. [3] Here, we present a case of a young male with TSC and multiple AMLs, containing RCC with eosinophilic morphology.…”
mentioning
confidence: 99%
“…Inomoto et al . [3] had reported one case of RCC originated in a previously existing AML and considered that RCC arose in the AML from the clinical and pathological point of view. However, other researchers suggested that AML and RCC were coincidentally present in the same tumor mass.…”
mentioning
confidence: 99%
“…Although isolated case reports of AMLs coexisting with a malignancy do exist, such lesions appear to be exceedingly rare. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Renal angiomyolipoma is usually a benign lesion, it can be rarely associated to renal adenocarcinoma (4,5) and to tuberous sclerosis. The histology shows mature adipose tissue, smooth muscle, and thick-walled blood vessels.…”
Section: Discussionmentioning
confidence: 99%